Knowledge and Practice in Cochlear Re-Implantation in the UK: A Survey for Audiologists - Muhammed Ayas; Rosalyn Parker; David Muir; Jameel Muzaffar (Audiology Research, 2024)
Background: Cochlear implantation (CI) has proven to be a highly effective method for rehabilitating individuals with severe to profound hearing loss. However, challenges persist, particularly in cases where CI failure necessitates re-implantation. This study aims to address the gap in understanding the knowledge and practices of audiologists in the UK regarding cochlear re-implantation through a comprehensive questionnaire survey. Methods: A bespoke questionnaire was distributed to audiologists working with CI across the UK. The survey, which included multiple-choice items, open-text responses, and visual analogue scales, was made accessible via an online link shared through professional bodies, email groups, and social media platforms. Results: The survey received 27 responses, predominantly from female audiologists (71.4%), with significant representation from London (28.6%) and the East of England (21.4%). A majority of respondents had over 16 years of CI experience (35.7%) and held a master’s degree (60.7%). Key reasons for CI re-implantation included electrode failure (82.1%) and hermetic seal failure (60.7%). While respondents showed strong confidence in counselling (88.8%) and managing re-implanted devices (84.6%), there was a noted variation in opinions regarding the need for additional training in intraoperative measures. Conclusion: This survey highlights the current practices and training needs of UK audiologists in CI re-implantation. This underscores the importance of targeted training to fill knowledge gaps and improve clinical care during CI re-implantation, ultimately enhancing outcomes for both audiologists and CI recipients.